2020
DOI: 10.1186/s12865-020-00374-9
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and reference ranges of CD4+T cell subpopulations among healthy adult Han Chinese in Shanxi Province, North China

Abstract: Background: Immunophenotyping of blood lymphocytes is an essential tool to evaluate the immune function of patients with immunodeficiency or autoimmunity. Predominately identified CD4 + T cell subsets, Th1, Th2, Th17, as well as regulatory T (Treg) cells, play crucial roles in several immunological and pathological conditions. Considering the variations in cell counts among populations and ethnicities, specific CD4 + T cell subset reference values need to be locally established to enable meaningful comparisons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
4
15
0
Order By: Relevance
“…Qin L et al [ 19 ] found that the correlation coefficients between CD3 + T cell count (cells/ul), CD3 + CD4 + T cell count (cells/ul), CD3 + CD8 + T cell count (cells/ul) and age were − 0.103, − 0.175, − 0.154. Our results are similar with Niu HQ et al [ 21 ] and Qin L et al [ 19 ] but slightly different from Tang GX et al [ 20 ]. The percent of CD3 + T cell, CD3 + CD8 + T cell and the numbers of CD3 + T cell count (cells/ul), CD3 + CD4 + T cell count (cells/ul), CD3 + CD8 + T cell count (cells/ul) were all weak negatively correlated with age in both male and female ( P < 0.01), while the percent of CD3 + CD4 + T cell was weak positively correlated with age in male but weak negatively in female ( P < 0.01).…”
Section: Discussionsupporting
confidence: 84%
See 4 more Smart Citations
“…Qin L et al [ 19 ] found that the correlation coefficients between CD3 + T cell count (cells/ul), CD3 + CD4 + T cell count (cells/ul), CD3 + CD8 + T cell count (cells/ul) and age were − 0.103, − 0.175, − 0.154. Our results are similar with Niu HQ et al [ 21 ] and Qin L et al [ 19 ] but slightly different from Tang GX et al [ 20 ]. The percent of CD3 + T cell, CD3 + CD8 + T cell and the numbers of CD3 + T cell count (cells/ul), CD3 + CD4 + T cell count (cells/ul), CD3 + CD8 + T cell count (cells/ul) were all weak negatively correlated with age in both male and female ( P < 0.01), while the percent of CD3 + CD4 + T cell was weak positively correlated with age in male but weak negatively in female ( P < 0.01).…”
Section: Discussionsupporting
confidence: 84%
“…The 2.5% to 97.5% reference ranges of percentages (absolute counts, cells/μl) CD3 + T cells, CD3 + CD4 + T cells, CD3 + CD8 + T cells in Tang GX et al 's research [ 20 ] and Qin L et al 's research [ 19 ] are shown in Additional file 1 : Table S1. Our results are similar with Niu HQ et al [ 21 ] and Tang GX et al [ 20 ] but slightly different from Qin L et al [ 19 ]. The discrepancy may be explained by different sample size, indirect method we used to establish reference value and the variance of ethnic groups.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations